The Individual Income Tax and Economic Growth : An International Comparison: France, Germany, Italy, Japan, United Kingdom, United States - Tanzi, Vito. (Baltimore : Johns Hopkins Press, 1969)
This book deals with the issue of sacrifice or burden connected with individual income tax; the relationship between the individual income tax and the propensity of the household sector to save ; the relationship of the individual income taxes of these countries to their economic growth.
Bibliography: p. 127-133.
osc 30/6/17
Loans
Keywords: Income tax; Economic Development